Produksi Kedelai pada Tumpang Sari dengan Tithonia diversifolia - Putri Mustika Sari; Adriansyah Yoesoep; Lisdayani Lisdayani (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2020)
Considering that soybeans are a food ingredient, it is necessary to control insect pests that are appropriate and environmentally friendly to increase soybean production, for example, through an intercropping pattern using flowering plants that can attract beneficial insects. This study aimed to increase soybean production by increasing the number of natural enemies planted through an intercropping soybean pattern with Titonia (Tithonia diversifolia). This research was conducted from April - August 2020 at Aras Kabu Village Deli Serdang District; the method used was direct observation to the experimental field of soybean – Titonia intercropping made with 5 Mapping spacing treatments. Harvesting insects using sweep net and for production is counted from soybean pods. The results showed that the soybean-Titonia intercropping had an effect on soybean production, the highest number of seeds was in the treatment of 50 cm spacing between plants (T4) of 57.33, and the highest weight of 100 seeds was in the treatment of 50 cm spacing between plants (T4) treatment of 15.22. The insect orders found in the area of Titonia-soybean intercropping plantations are Hemiptera, Coleoptera, Diptera, Hymenoptera, Lepidoptera, where many predatory insects, parasitoids, and pollinators are found. Judging from the content of secondary metabolites of Titonia, namely alkaloids, tannins, and flavonoids, the results of Titonia plants, including flower, stems, and leaves, can be used to extract pesticides in controlling insect pests.